Methods and tools of anticyclical management in construction – social aspect - Loktionova , Ya. (Ways to Improve Construction Efficiency, 2025)
The article carries out a comprehensive study of methods and tools of anticyclical management in construction, taking into account their social effectiveness in conditions of growing economic turbulence. It is shown that the construction industry is one of the most dependent on economic cyclicality, as it reacts to fluctuations in investment demand, availability of financial resources, cost of materials and the state of the labor market. It is established that economic downturns lead to a reduction in employment, a decrease in employee income, a slowdown in the implementation of infrastructure projects and a deterioration in social stability in the regions. The work systematizes key groups of anticyclical methods – fiscal-budgetary, credit-financial, production-technological, personnel-social, market and strategic – and identifies specific tools that ensure their implementation. Particular attention is focused on the social effects of the use of these tools: preserving jobs, improving personnel skills, improving housing availability, strengthening infrastructure security and improving the quality of the living environment. It is proven that the integration of state investment programs, tax incentives, preferential lending mechanisms, digital project management technologies, as well as diversification of the construction work portfolio can mitigate the negative impact of economic downturns and generate additional social results. It is substantiated that socially oriented countercyclical management is a necessary condition for the sustainable functioning of construction enterprises and ensuring the long-term development of the industry. Prospects for further research lie in modeling the dynamics of cyclical processes, assessing the social effectiveness of anticyclical measures at the regional level and adapting international approaches to the specifics of the Ukrainian construction sector.